Comparing physiological and psychological effects of virtual reality vs. traditional high-intensity interval training in healthy individuals: results from a preliminary pilot randomised controlled trial - Jonathan Robinson; Mohammad Haziq Bin Abdul Razak (Bulletin of Faculty of Physical Therapy)
Abstract Background Physical inactivity is a growing concern, contributing significantly to the development of chronic diseases. Virtual reality and active video games have emerged as potential solutions to promote physical activity by integrating immersive experiences with exercise. High-intensity interval training (HIIT) is a time-efficient method for improving fitness, but its intensity may reduce motivation. Recent studies suggest that virtual reality (VR) could enhance both the psychological experience and motivation to engage in exercise, making it a promising alternative to traditional HIIT training. Objectives The study aimed to explore the feasibility, efficacy, and potential effects of VR compared to traditional HIIT in terms of physiological and psychological outcomes in physically active adults. Methods Using a parallel-design pilot randomised controlled trial, 10 participants completed the study and were randomly allocated to either the VR group (n = 5) or non-VR group (n = 5). The VR group participated in a single session of HIIT using the Facebook Oculus Quest 2 VR headset, while the non-VR group underwent a single session of traditional HIIT training. Physiological outcomes, including heart rate parameters (measured using a Polar HR monitor) and rating of perceived exertion (RPE, assessed using the Borg scale), as well as psychological outcomes of the flow experience (measured using the Flow State Scale questionnaire) were assessed. Results Statistical analysis showed no significant difference in heart rate parameters between the VR and non-VR groups, indicating that both interventions achieved comparable exercise intensity and meeting the recommended levels for health benefits. However, the VR group demonstrated a lower RPE score (p < 0.001, d = − 3.7; BF 10 = 58.7), suggesting a reduced perception of effort during the exercise session compared to the non-VR group. Additionally, the VR group reported a significantly higher post-intervention flow state score — a state of deep focus and immersion — in the subscale of unambiguous feedback (p = 0.04, d = 1.6; BF 10 = 2.2), reflecting clear, immediate feedback and a more engaging, intrinsically motivating exercise experience. Conclusions This pilot study suggests that fully immersive VR can be an effective alternative to traditional HIIT, providing a high-flow experience and potentially enhancing motivation among physically active users. Trial registration ClinicalTrials.gov, NCT06420414. Registered 20 May 2024 — retrospectively registered, https://clinicaltrials.gov/study/NCT06420414